PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN SIAK (STUDI KASUS PELAYANAN NON PERIZINAN) - Riana Savitri; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Implementation of the Integrated Administration Service Subdistrict Administrative Services in District Siak of which has been running since launched in 2012 has been successful. It is marked by the elected of a Subdistrict of Siak as Sub district of Operator's Best PATEN Riau Province in 2012 and was also elected as the Sub district of Pilot Implementation PATEN in Riau Province in 2013. This study was conducted to determine how the implementation of PATEN in Sub district Siak and factor- factors that affect of successful implementation in the district PATEN Siak.Research conducted using qualitative method with descriptive research. This study uses the theory of dimensions of quality service by Agus Dwiyanto consisting of attitude of officers, procedures, time, facilities, and costs of service. In this research have some technique conducted by using observation, interviews and documentation with literature study by using descriptive analysis techniques.These results indicate that the implementation of the PATEN in Subdistrict Siak has qualified. It is characterized by an attitude PATEN officers who have good and friendly, service procedures are simple and clear, time services corresponding with the standards of service, facilities suffice to community and officers, and the cost of services in accordance with the information and existing standards service. In addition, the commitment of the government and good support from the community has made implementation in the Subdistrict PATEN Siak successfully.Keywords: Implementation, Service, PATEN Subdistrict of Siak